Análise eco-epidemiológica da leishmaniose tegumentar americana em uma área endêmica da microrregião de Caratinga, Minas Gerais (Brasil), submetida a ensaio comunitário com vacina antilta. - Simone Marrocos de Resende (2004)
Cutaneous Leishmaniasis (ACL) is a transmitted disease complex psycho-social impact and public health, such as high morbidity and mortality due to Texico treatment. Objeticou to characterize the ecology and epidemiology of the disease and temporal and spatial distribution of cases, study the environmental and conduct qualitative research flobotomíneos species. He worked in the municipalities of the region of Caratinga: Bom Jesus do Branch, Caratinga, New Creek, Between Leaves and Ubaporanga. Were pre-selected five rural areas in each municipality based on retrospective analysis of cases between 2001-2002 to obtain demographic and clinical data. Subsequently, these areas were subjected to the test with vaccine antiLTA Community. The results showed the cyclical nature of ATL next six years, peridomestic transmission profile, predominantly in men and farmers. The way the clinical manifestations were cutaneous, the extremities are the most affected (51%). As for the categorization of land use was predominantly grassland (66%), reforestation (14%), poultry (11%) and low level of remaining natural forest (0.5%). Of the population surveyed (9,600 people) made up four groups: those eligible for testing (MST-negative 85.5%) who received vaccine or placebo antiLTA; the immune (MST positive - 4%) patients (active or healed wound 2 9%) and with exclusion criteria (0.4%). Entomological surveys in the most frequent species was Lutzomyia intermediate